Implementasi Peraturan Daerah Provinsi Bali Nomor 16 Tahun 2009 Tentang Rencana Tata Ruang Wilayah Provinsi dalam Penguasaan dan Pemanfaatan Wilayah Pesisir - Ni Wayan Kertiasih; I Made Suwitra; I Nyoman Sujana (Jurnal Konstruksi Hukum, 2020)
This research aims to analyze the implementation of local regulations regarding Bali province Number of 16 2009 about Spatial Plan Area of Bali in the mastery and the utilization of the coastal area associated with mastery and authority utilization over the coastal areas as well as analyzing the related strategies of mastery and the utilization of the coastal area. The type of research used in the form of empirical legal research, using the approach the approach to legislation, a legal concept analysis approach, the approach of anthropological approach and the case law. The data source of this research was obtained from primary data and secondary data, collected with the stages through the interview techniques and engineering studies and subsequent documents processed and analyzed qualitatively with systematic way, classified in the pattern and themes, classified, connected between each other, to understand the significance of data interpretation in social situations, and the interpretation of the overall data quality. Research results show that the authority of the mastery and the utilization of the coastal area after the passage of the ACT Government is the authority of the Central Government and the regional Government of the province which is practically given delegates to the district/city Governments overseeing the mastery and its utilization by local community. Setting against the mastery and the utilization of the coastal area of Bali should be established with local regulations, and as it is known that these provisions (RZWP3K settings) are still in the drafting stage so that the top recommendations submission of mastery and the utilization of the coastal area in the province of Bali has yet to be implemented effectively.